Non-timber forest products and trade in eastern Borneo - Sellato, B. (2002)
A broad range of non-timber forest products of plant and animal origin collected from the Borneo rain forestand subsequently traded are presented. These products include resins, latex, rattans and birdsnests. The article discusses their local and regional uses and whether they are or have been targeted for local or international markets. The author also presents for the northern part ofthe Indonesian province of East Kalimantan a history of trade in these products based on various written (Dutch colonial archives, official Indonesian statistics, local scholarly texts) and oral (interviews with nomadic Punan people, Dayak swidden farmers, Malays in the coastalports, Chinese and Arab traders, middlemen disseminating in land products on international markets) sources. This historical reconstruction suggests that despite the fact that some of these products have been traded on world markets for almost two millenia their systematic and unsustainable exploitation only began in the 17th century. Since then, the products have been extracted along a front that has gradually progressed from the coastal regions via the rivers towards interior parts ofthe island. This exploitation ended inthe 1990s, with almost complete depletion of these resources. The local forest communities (Dayak and Punan) are neither wise conservationists nor primitive destroyers of the forest, but simply economic stakeholders. Their sensible, pragmatic strategies have enabled their long term survival in local forests underany circumstances with respect to world market demand.